Model Analysis of FDD-LTE Forward Interference and Capacity - Ge Zhou; Junwen Wang (Dianxin kexue)
The forward interference is an important factor that affects the FDD-LTE network capacity and user experience. FDD-LTE forward interference and capacity were analyzed. A forward interference model was proposed under various network loads. Simulation result of ideal and practical network is approximate to the road test result. The model provides evaluation method with high precision for practical business network and it can provide important information for business development and network invest.